2019
DOI: 10.1021/acs.nanolett.9b03416
|View full text |Cite
|
Sign up to set email alerts
|

Large Current Driven Domain Wall Mobility and Gate Tuning of Coercivity in Ferrimagnetic Mn4N Thin Films

Abstract: Spintronics, which is the basis of a low-power, beyond-CMOS technology for computational and memory devices, remains up to now entirely based on critical materials such as Co, heavy metals and rare-earths. Here, we show that Mn4N, a rare-earth free ferrimagnet made of abundant elements, is an exciting candidate for the development of sustainable spintronics devices. Mn4N thin films grown epitaxially on SrTiO3 substrates possess remarkable properties, such as a perpendicular magnetisation, a very high extraordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 40 publications
4
47
0
Order By: Relevance
“…Recent experiments have shown that epitaxial Mn 4 N thin films exhibit a perpendicular magnetization, remarkable magnetic properties within particular millimetric and smooth DWs, 18 and record DW velocities owing to spin transfer torque. 19 As such, we have focused on ferrimagnetic Mn 4 N doped with Ni to obtain a material close to magnetic compensation at room temperature (RT). Using neutron diffraction, the magnetic moment of the Mn atoms in bulk cubic Mn 4 N was measured and it was found to be 3.53 μ B at the corner sites (I sites) and −0.89 μ B at the face-centered sites (II sites), 20 as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments have shown that epitaxial Mn 4 N thin films exhibit a perpendicular magnetization, remarkable magnetic properties within particular millimetric and smooth DWs, 18 and record DW velocities owing to spin transfer torque. 19 As such, we have focused on ferrimagnetic Mn 4 N doped with Ni to obtain a material close to magnetic compensation at room temperature (RT). Using neutron diffraction, the magnetic moment of the Mn atoms in bulk cubic Mn 4 N was measured and it was found to be 3.53 μ B at the corner sites (I sites) and −0.89 μ B at the face-centered sites (II sites), 20 as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we achieved a v DW of 900 m/s at j = 1.2 × 10 12 A/m 2 for a Mn 4 N nanowire grown on STO(001) without applying an external magnetic field. 19 Substituting other transition metal atoms for Mn atoms in Mn 4 N is an effective way of modifying the material's magnetic properties. In previous studies, we grew Co x Mn 4−x N 23 and Fe 4−x Mn x N 26 epitaxial thin films by molecular beam epitaxy (MBE) and investigated their crystalline qualities and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Total simulated space is 300 nm x 300 nm x 15 nm in micromagnetic simulations, and each cell size is 5 nm x 5 nm x 5 nm. For these simulations, the exchange stiffness constant (A) is 1.5 x 10 − 11 J/m, estimated from Curie temperature of 745 K 24 . Saturation magnetization Ms is 50 kA/m and anisotropy K u is between 0.7 and 1.1 x 10 5 J/m 3 , based on the previous measurements 27 .…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…One promising candidate with superior thermal stability compared to the amorphous rare-earth transition metals is rare-earth-free Mn 4 N. There are some key similarities and differences between the rare-earth transition metals and Mn 4 N. Both are ferrimagnetic metals, and there have been successful experimental demonstrations of thin film growth in both systems. Both materials show perpendicular magnetic anisotropy (PMA) in the thin film geometry 16,[20][21][22][23][24][25][26][27] . However, unlike the amorphous structure in the rare-earth transition metals, Mn 4 N is a crystalline compound that forms in the anti-perovskite crystal structure 27 .…”
mentioning
confidence: 99%
See 1 more Smart Citation